Availability of Health Services through Health Insurance Schemes in Tanzania - Ndunguru, Moses January (Journal of Policy and Leadership, 2022)
This article presents citizens' perceptions of the availability of health services through community-based health insurance schemes in Tanzania as of 2015. A descriptive crosssectional design involving qualitative and quantitative methods was adopted to collect data from 433 individuals in six districts of Tanzania's mainland. Data collected through questionnaires, in-depth interviews, focus group discussions, and documentary reviews were analysed descriptively and thematically. The results indicated that the unavailability of health services is still a challenge for insured poor households in Tanzania. This is due to inadequate health facilities, frequent drug stock out, shortage of health workers and equipment, long distance to health facilities, especially in rural areas, and long waits for consultations. This bears on the inadequate availability of health services for poor households in the study areas. Therefore, scaling up the availability of health services through health insurance, efforts to make health facilities available and closer to people, sufficient supply of drugs, health workers, and equipment, and short waits for health services are important.